4(3z-3)=-6z+2

Simple and best practice solution for 4(3z-3)=-6z+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3z-3)=-6z+2 equation:



4(3z-3)=-6z+2
We move all terms to the left:
4(3z-3)-(-6z+2)=0
We multiply parentheses
12z-(-6z+2)-12=0
We get rid of parentheses
12z+6z-2-12=0
We add all the numbers together, and all the variables
18z-14=0
We move all terms containing z to the left, all other terms to the right
18z=14
z=14/18
z=7/9

See similar equations:

| 16z-14z+5z=7 | | 31(1x)=37 | | (1/4)^3z-1=16^z+2*64^z-2 | | 5j-5j+4j=8 | | 30(0x)=37 | | 29(0x)=37 | | 1/3(18x+21)-5=-1/5(10x-15) | | 12n+3n+n-2n=18 | | x2-16x+12=0 | | 28(x)=37 | | 14k+2k-13k-2k=8 | | 27(3x)=37 | | 6w-4w=8 | | 12d-11d=18 | | 10t-7t=6 | | 26(3x)=37 | | 25(0x)=37 | | 24(x)=37 | | .40c+.75C=235 | | 23(0x)=37 | | 22(0x)=37 | | 28.50/9=m/2 | | 21(0x)=37 | | 10x^2+750x+59000=1000x+22000 | | 5*x+10=5 | | (8x-9-2x)=(15+5x-5) | | 17-3x=-16 | | 1700/8=120/x | | 2(x+3)^(1/4)-5=1 | | 5*x-0=5 | | 25x2+49=70x | | 5*0-y=5 |

Equations solver categories